Análise da vulnerabilidade natural da perda de solos na bacia hidrográfica do Ribeirão Vermelho/MS - ADRIANA BILAR CHAQUIME DOS SANTOS (2022)
In order to demonstrate the weaknesses and potentialities that exist in the region, the chosen cut was the watershed of Ribeirão Vermelho, in the municipalities of Aquidauana and Dois Irmãos do Buriti, inserted in the watershed of the Miranda River. In this perspective, the general objective of the research is to identify the natural vulnerability to soil loss of the Ribeirão Vermelho Watershed in relation to soil loss. According to the methodology used, the degree of vulnerability of the basic territorial units is identified based on morphogenesis and pedogenesis, with attribution of degrees of vulnerability to each landscape unit, namely: Geology, Geomorphology, Soil, Climate and Vegetation Cover. Thematic maps were developed in QGIS 3.16 Hannover software, then weighting was applied. The results obtained show that 82.71% of the area is considered as moderately vulnerable, with morphogenesis processes prevailing; the moderately stable/vulnerable class corresponds to 17.29% of the basin; occurs in specific areas, mostly in the lower and middle course of the river, considered an environment with intermediate situations, and there is a balance between morphogenesis and pedogenesis. Therefore, the study on the natural vulnerability to soil loss of the Ribeirão Vermelho watershed showed that this basin is naturally predisposed to morphogenic processes and that, although it presents vulnerable areas, it can maintain and enhance the conservation of vegetation, which is a essential natural territorial unit to mitigate erosion and soil loss.